Right intrathoracic ectopic kidney and pulmonary sequestration associated with right sided congenital diaphragmatic hernia - Jinyoung Park (Elsevier, 2020)
Intrathoracic ectopic kidney is an uncommon congenital anomaly, accounting for approximately 5% of all ectopic kidneys. An intrathoracic ectopic kidney and pulmonary sequestration associated with a congenital diaphragmatic hernia is a very rare condition. This study describes a patient with a right intrathoracic ectopic kidney and pulmonary sequestration associated with right sided congenital diaphragmatic hernia. Contrast-enhanced chest computed tomography showed a right intrathoracic ectopic kidney and lung mass with herniation of the right lobe of the liver through the right diaphragmatic defect. The herniated intestine, the right lobe of the liver and the right intrathoracic ectopic kidney were relocated into the abdomen, followed by excision of the pulmonary mass and closure of the diaphragmatic defect with Permacol.